Professional agriculture: the Fulani in Central Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Many farmers' organizations have been formed in Africa since the 1980s. Farmers formed groups to achieve recognition, improve the protection of their interests and to restore functions once performed by the government but which they are now in a...